2019
DOI: 10.1186/s41100-019-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical prevention strategy for arteriovenous fistula and arteriovenous graft failure

Abstract: Vascular access failure (VAF) is a critical problem in patients undergoing hemodialysis (HD). Importantly, VAF impairs the quality of life in patients undergoing HD while imposing high medical costs. A variety of strategies (e.g., endovascular therapy and surgical reconstruction) for treating VAF have been established. However, strategies for preventing VAF are scarce. In this review, we summarized the available literatures regarding the prevention of VAF in patients undergoing HD with a focus on arteriovenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 91 publications
0
4
0
1
Order By: Relevance
“…The demographic factors including age, sex, and ethnicity; the clinical factors such as heart disease, peripheral arterial disease, diabetes mellitus, obesity, etc. ; the hemodynamic factors consisting of the size and diastolic function of vessels, blood flow, etc., and the technical factors such as the experience of the surgeon and the cannulation techniques employed during dialysis are the common causes for AVF failure [ 6 ]. Early thrombosis of fistula is mostly caused because of an inflow problem due to juxta-anastomosis stenosis or accessory vein, while the late thrombosis tends to be due to outflow stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The demographic factors including age, sex, and ethnicity; the clinical factors such as heart disease, peripheral arterial disease, diabetes mellitus, obesity, etc. ; the hemodynamic factors consisting of the size and diastolic function of vessels, blood flow, etc., and the technical factors such as the experience of the surgeon and the cannulation techniques employed during dialysis are the common causes for AVF failure [ 6 ]. Early thrombosis of fistula is mostly caused because of an inflow problem due to juxta-anastomosis stenosis or accessory vein, while the late thrombosis tends to be due to outflow stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings suggest that few prophylactic drugs effectively prevent VA failure for AVF and AVG, and no strong evidence indicates the efficacy of any medications in reducing the incidence of VA failure. 37 Regardless, our study suggests that the use of the prescribed medications alone or in combination may not always have a beneficial effect on vascular patency.…”
Section: Discussionmentioning
confidence: 71%
“…Various trials showed that anticoagulation therapy, including the use of heparin or oral anticoagulants, had higher risks of bleeding complications and did not prevent access failure. Likewise antiplatelet aggregation with agents such as dipyridamole and clopidogrel increased the risk of bleeding events and did not prevent AVG thrombosis ( 84 ). Omega 3 polyunsaturated fatty acids (PUFAs) have anti-inflammatory, antiproliferative, anti-platelet aggregation activity and vasodilatory effects, and have been used in different clinical trials to assess their benefits on the prevention of stenosis.…”
Section: Arteriovenous Graftsmentioning
confidence: 99%